BRIDGING GLOBAL TAX REFORM AND SUSTAINABLE DEVELOPMENT: A BIBLIOMETRIC OVERLAY OF INTERNATIONAL TAXATION LITERATURE - Cintyawati, Kirana; Setijaningsih, Herlin (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2026)
The growth of the digital economy has challenged traditional tax principles and created difficulties for fiscal systems worldwide, particularly in developing economies. This paper examines international tax research published between 2005 and 2025, with a focus on the OECD/G20 Two-Pillar Solution and its implications for global tax policy. Following the PRISMA 2020 guidelines, 99 Scopus-indexed publications were analyzed using keyword co-occurrence mapping, citation tracking, journal quartile distribution, and co-authorship network analysis. The findings reveal an acceleration in publications after 2019, three thematic clusters, citation dominance by Q2 journals, limited alignment with the SDGs, and a need for simplified rules and capacity building in developing economies. This study contributes by tracing the evolution of international tax research from the BEPS project to the Two-Pillar framework, identifying thematic clusters and collaboration networks, assessing intersections with the UN Sustainable Development Goals, and highlighting theoretical and practical implications for Indonesia and other developing economies.